Green practices of small island chalet operators in East Peninsular Malaysia - Yusof, Zeenat Begam; Jamaludin, Mariam (Elsevier, 2015)
The uncontrolled lodging industry usually caused environmental degradation. However, some lodging operators have started to incorporate green practices in their operation. The objectives of this study are to identify green practices of Small Island Chalets (SICs) operators in Kapas and Tioman Island in Malaysia and to determine the differences of the green practices on the both islands. This study had employed case study method using in-depth interview and structured observation. Six case studies were selected. The findings had identified the difference and several green practices of the operators. Therefore, this study provides a platform for another similar study to be conducted.